WATCHING ENGLISH MOVIE ON IMPROVING STUDENTS' WRITING ABILITY - Lastry Forsia (PRIMACY Journal of English Education and Literacy, 2022)
This research aims to investigate whether there is a significant effect of watching English movie on improving students’ ability to write a narrative text at the tenth-grade students. This research used quasi experimental method. Sample of the study consisted of 76 students. The sampling technique was used random sampling. In this research, the researcher used to watch English movie to improve students’ writing ability to trigger ideas. This research consisted of three stages. The first stage was pre-test giving stage. The second was treatment implementation stage, namely watching English movie as a technique in experiment class and without watching English movie in controlled class. The third was post-test giving stage. The type of the research was written test. To validate the instrument, the writer asked an expert to validate its content. This instrument was said valid. Then, the results of both classes were analyzed by using t-test. The study findings revealed that there were significant differences between the mean scores attained by the experimental class and control class. Post intervention data indicated a remarkable increase in the experimental class’ achievement in writing ability with the result found that tobserved > ttable for the significant level (0,025), 2,72 > 2. So, Ho is rejected, and Ha is accepeted. It means that there is significant effect of watching English movie on improving students’ ability to write a narrative text at the tenth grade of SMAN 12 Kabupaten Tangerang in academic year 2021/2022